2014
DOI: 10.3109/02713683.2014.905609
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Source of Incisional Vitreous Incarceration on Sclerotomy Closure Competency after Transconjunctival Sutureless Vitrectomy

Abstract: Sclerotomies with vitreous incarceration coming from the core of the vitreous cavity showed a greater incisional closure competency than that observed in incisions with vitreous entrapment coming from the pericannular area; if these results were confirmed in humans, different postoperative suture rates may be expected on sclerotomies according to the vitrectomy degree performed in different areas of the vitreous cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…In this respect, the characteristics of our populations, valved or nonvalved, at the end of the procedure are very similar, because both valved and nonvalved cannula extraction was performed without pulling the vitreous inside the eye, as the light probe does. 11 Moreover, Benitez-Herreros et al 13 found that the source of the incarcerated vitreous, core or pericannular, was related to different closure competencies at the 23-gauge sclerotomy site in their animal model. This implies that the vitrectomy degree may alter the amount of vitreal incarceration 13 and confirms the previous finding in 20-gauge surgery of Sabti et al, 16 who found that the vitreous shaving of sclerotomy sites with scleral indentation significantly reduced vitreous incarceration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this respect, the characteristics of our populations, valved or nonvalved, at the end of the procedure are very similar, because both valved and nonvalved cannula extraction was performed without pulling the vitreous inside the eye, as the light probe does. 11 Moreover, Benitez-Herreros et al 13 found that the source of the incarcerated vitreous, core or pericannular, was related to different closure competencies at the 23-gauge sclerotomy site in their animal model. This implies that the vitrectomy degree may alter the amount of vitreal incarceration 13 and confirms the previous finding in 20-gauge surgery of Sabti et al, 16 who found that the vitreous shaving of sclerotomy sites with scleral indentation significantly reduced vitreous incarceration.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Moreover, Benitez-Herreros et al 13 found that the source of the incarcerated vitreous, core or pericannular, was related to different closure competencies at the 23-gauge sclerotomy site in their animal model. This implies that the vitrectomy degree may alter the amount of vitreal incarceration 13 and confirms the previous finding in 20-gauge surgery of Sabti et al, 16 who found that the vitreous shaving of sclerotomy sites with scleral indentation significantly reduced vitreous incarceration. By including only epiretinal membrane and MH eyes, we reduced the bias linked to the extent of vitreous removal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pars plana vitrectomy (PPV) is considered a standard surgical approach in many vitreoretinal diseases. However, PPV can lead complications, some of which arise from the changes in anterior segment morphology [4]- [11].…”
Section: Introductionmentioning
confidence: 99%